A new species of Vargapupa Páll-Gergely, 2015 and a new synonym of Pseudopomatias Möllendorff, 1885 (Gastropoda: Caenogastropoda: Pupinidae) - Páll-Gergely, Barna (Zootaxa, 2016)
Revision of the genus Pseudopomatias Möllendorff, 1885 and its relatives (Páll-Gergely et al. 2015) resulted in the recognition of four genera, which agree in the (usually slender) turriform, spindle-shaped or almost cylindrical shell and the regularly ribbed teleoconch, except sometimes for the last half whorl. The genus Vargapupa Páll-Gergely, 2015, which differs from Pseudopomatias by possessing a basal keel, includes two species, one from Vietnam, and another from Laos.